Regulation and Role of GLI1 in Cutaneous Squamous Cell Carcinoma Pathogenesis - Pyczek, Joanna; Khizanishvili, Natalia; Kuzyakova, Maria; Zabel, Sebastian; Bauer, Julia; Nitzki, Frauke; Emmert, Steffen; Schön, Michael P.; Boukamp, Petra; Schildhaus, Hans-Ulrich; Uhmann, Anja; Hahn, Heidi (Frontiers in Genetics, 2019)
Cutaneous squamous cell carcinoma (cSCC) is the second most common skin tumor in humans. Although current therapies are sufficient to clear the tumor in many cases, the overall risk of cSCC metastasis is still 5 %. Alternative treatment options could help to overcome this situation. Here we focused on the role of the Hedgehog (HH) signaling pathway and its interplay with epidermal growth factor receptor (EGFR) signaling in cSCC. The analyses revealed that, despite lack of sonic HH (SHH) expression, a subset of human cSCC can express GLI1, a marker for active HH signaling, within distinct tumor areas. In contrast, all tumors strongly express EGFR and the hair follicle stem cell marker SOX9 at the highly proliferative tumor-stroma interface, whereas central tumor regions with a more differentiated stratum spinosum cell type lack both EGFR and SOX9 expression. In vitro experiments indicate that activation of EGFR signaling in the human cSCC cell lines SCL-1, MET-1 and MET-4 leads to GLI1 inhibition via the MEK/ERK axis without affecting cellular proliferation. Of note, EGFR activation also inhibits cellular migration of SCL-1 and MET-4 cells. Because proliferation and migration of the cells is also not altered by a GLI1 knockdown, GLI1 is apparently not involved in processes of aggressiveness in established cSCC tumors. In contrast, our data rather suggest a negative correlation between Gli1 expression level and cSCC formation because skin of Ptch+/- mice with slightly elevated Gli1 expression levels is significantly less susceptible to chemically-induced cSCC formation compared to murine wildtype skin. Although not yet formally validated, these data open the possibility that GLI1 (and thus HH signaling) may antagonize cSCC initiation and is not involved in cSCC aggressiveness, at least in a subset of cSCC.